The Effect of Patient Portals on Quality Outcomes and Its Implications to Meaningful Use: A Systematic Review - Kruse, Clemens Scott; Bolton, Katy; Freriks, Greg (JMIR Publications, 2015)
BackgroundThe Health Information Technology for Economic and Clinical Health (HITECH) Act imposes pressure on health care organizations to qualify for "Meaningful Use". It is assumed that portals should increase patient participation in medical decisions, but whether or not the use of portals improves outcomes remains to be seen. ObjectiveThe purpose of this systemic review is to outline and summarize study results on the effect of patient portals on quality, or chronic-condition outcomes as defined by the Agency for Healthcare Research and Quality, and its implications to Meaningful Use since the beginning of 2011. This review updates and builds on the work by Ammenwerth, Schnell-Inderst, and Hoerbst. MethodsWe performed a systematic literature search in PubMed, CINAHL, and Google Scholar. We identified any data-driven study, quantitative or qualitative, that examined a relationship between patient portals, or patient portal features, and outcomes. We also wanted to relate the findings back to Meaningful Use criteria. Over 4000 articles were screened, and 27 were analyzed and summarized for this systematic review. ResultsWe identified 26 studies and 1 review, and we summarized their findings and applicability to our research question. Very few studies associated use of the patient portal, or its features, to improved outcomes; 37% (10/27) of papers reported improvements in medication adherence, disease awareness, self-management of disease, a decrease of office visits, an increase in preventative medicine, and an increase in extended office visits, at the patient's request for additional information. The results also show an increase in quality in terms of patient satisfaction and customer retention, but there are weak results on medical outcomes. ConclusionsThe results of this review demonstrate that more health care organizations today offer features of a patient portal than in the review published in 2011. Articles reviewed rarely analyzed a full patient portal but instead analyzed features of a portal such as secure messaging, as well as disease management and monitoring. The ability of patients to be able to view their health information electronically meets the intent of Meaningful Use, Stage 2 requirements, but the ability to transmit to a third party was not found in the review.